ANALISIS MODAL KERJA TERKAIT DENGAN RENTABILITAS PADA PT PERKEBUNAN NUSANTARA VII (PERSERO) - Rina Milyati Yuniastuti (Sekolah Tinggi Ilmu Ekonomi Gentiaras, 2011)
The main purpose of the analysis of the sources and use of funds is to find out how thefunds are used and how the need for these funds are spent. To realize all these demands requires aprinciple of effective management and efficient and productive to all parts of the company, andsupported by an effective control measures to prevent irregularities that interfere with theperformance of the company.One of the company's goal is to obtain profits in general accordance with the previouslyplanned. It required an explanation that efektiff and efficiently over existing resources. In an effort torealize the efficient operation of the company, the measure of success is not enough just seen fromthe profits earned, but must be viewed from rentabilitasnya. Venture company should be directed tothe achievement of maximum profitability levels.